(untitled) (LACCEI, 2024)
This work aims to show bioconstruction with different constructive alternatives. It is done by going through various cases, in which several of the members of this work participated. They show different construction techniques such as: adobe, quincha, pallets with bottles, direct modeling and superadobe. In addition, it seeks to disseminate it, since it is an alternative for the reduction of greenhouse gases, among other things because the materials do not travel or have a minimum of transport since they are mostly local and the energy to obtain them is lower. than in traditional construction. The use of natural or recycled materials, in addition to being able to be reused, provide a habitat with thermal comfort, reducing energy costs for heating and cooling. In conclusion, we can say that these types of constructions can be carried out in different regions, using their native and nearby natural resources, they can also be applied to different social classes, for self-construction and different applications of use.